ОНЛАЙН АРДЧИЛЛЫН БЭХЖИЛТ БА МОНГОЛЫН УЛС ТӨРИЙН НАМЫН ГИШҮҮНЧЛЭЛД ТУЛГАРЧ БУЙ СОРИЛТУУД - С.Мөнхбат; Н.Батсүмбэрэл (Politology, 2023)
Political party is the main institution of representative democracy. On the other hand, it is the main tool of the republican state. Considering the above two meanings, the political party is an important organization of representative democracy and political aggregation performs the role of "mediator" between the state and citizens. In this article, we aim to changes in modern party membership and the challenges of Mongolian political party’s membership